Stabilization of the Interaction of the Compunds of Mallotus paniculatus Müll.Arg. on Gluthations S-Transferase (GSTs) - Samsul Hadi (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Gluthathione s-transferases (GSTs) play an important role against carcinogens, therapeutic drugs, and various types of cellular oxidative damage. Judging from its role in overcoming cellular oxidative damage, the activity of GSTs is one of the antioxidant enzymes. One of the plants that has been tested for its antioxidant ability is M. paniculatus. The content of M. paniculatus has been found so that it can be used to test the stability of the interaction between ligands and receptors. The aim of this research is to find compounds from M. paniculatus that have the potential to stabilize the interaction with the receptors. This docking method begins with ligand preparation and protein preparation followed by docking, visualization of interactions and analysis of the results. The research resulted in various docking scores with the various proteins involved. The stability of the interaction is obtained when the ligand binds to Glutathione S-transferase type A3 is hesperetin, sitosterol and sitosterol, to Glutathione S-transferase type theta-2 is β-daucostero, to Glutathione S-transferase type P is quercetin. Keywords: GSTs, M. paniculatus, docking